Family Presence in the Adult ICU During Bedside Procedures. (July 2019) - Jakab, Marnie; Day, Alex Z.; Kraguljac, Alan; Brown, Maedean; Mehta, Sangeeta
Purpose: To understand perspectives of family members of adult patients admitted to the medical–surgical intensive care unit (ICU) regarding their presence during procedures. Methods: Respondents completed a questionnaire about procedures the patient had undergone, their desire to be present, and their experience. Procedures of interest were endotracheal intubation; chest compressions; vascular catheter insertion; and gastric, chest, and rectal tubes. Impact of Events Scale–Revised (IES-R) was completed at the time of questionnaire completion and again 1 month later to evaluate the psychological impact of witnessing a procedure. Results: Ninety-seven respondents completed the questionnaire on behalf of 72 patients. More than 90% patients had at least 1 procedure. Only 29 (30%) family members were present for at least 1 procedure, and 44% to 100% wished to be present. Of the 68 respondents not present for a procedure, 18 (26.5%) wanted to be present. The IES-R was completed by 52 (95%) of 55 respondents who witnessed any procedure at time 1 and 28 (51%) of 55 respondents at time 2; mean IES-R scores were 8.0 and 8.8 ( P = .68), respectively. Only 2 participants had IES-R >33, signifying the likely presence of posttraumatic stress disorder. Conclusion: Family members wish to be present for ICU procedures, and there are no adverse psychological effects.